Coaggregation between Aquatic Bacteria Is Mediated by Specific-Growth-Phase-Dependent Lectin-Saccharide Interactions - Rickard, Alex H. (American Society for Microbiology, 2000)
Coaggregating strains of aquatic bacteria were identified by partial 16S rRNA gene sequencing. The coaggregation abilities of four strains of Blastomonas natatoria and one strain of Micrococcus luteus varied with culture age but were always maximum in the stationary phase of growth. Each member of a coaggregating pair carried either a heat- and protease-sensitive protein (lectin) adhesin or a saccharide receptor, as coaggregation was reversed by sugars.